Laparoscopic‐assisted liver transplantation: A realistic perspective. Issue 12 (2nd July 2022) - Dokmak, Safi; Cauchy, François; Aussilhou, Béatrice; Dondero, Fédérica; Sepulveda, Ailton; Roux, Olivier; Francoz, Claire; Hentic, Olivia; de Mestier, Louis; Levy, Philippe; Ruszniewski, Philippe; Ronot, Maxime; et al.
Abstract : Laparoscopic approach was rarely described in recipients for liver transplantation (LT). We report the feasibility and safety of laparoscopic‐assisted LT (LA‐LT) in patients with unresectable liver metastases of neuroendocrine tumors. Total hepatectomy was performed laparoscopically with graft implantation through an upper midline incision. Liver grafts were retrieved from deceased donors. From July 2019 to July 2021, six patients (4 women, 2 men) underwent LA‐LT. Median age and BMI were 46 (29–54) and 24 (19–35) kg/m 2, respectively. Implanted grafts were reduced ( n = 3), full ( n = 2), and a right split liver ( n = 1). Median surgical time was 405 min (390–450) and median blood loss was 425 ml (250–600). Median cold and warm ischemia times were 438 min (360–575) and 35 min (30–40), respectively. Median anhepatic phase was 51 min (40–67) and midline incision was 14 cm (13–20) long. On postoperative day 5, median prothrombin index and serum bilirubin levels were 95% (70–117) and 11 (10–37) μmol/L, respectively. No Clavien‐Dindo > III complications were encountered. Median hospital stay was 12 days (10–14). After a median follow‐up of 8 (8–32) months, all patients were alive without tumor recurrence or adverse event. This preliminary series suggests that in selected patients, LA‐LT is a safe and effective option. Abstract : A series of successful laparoscopically assisted liver transplantation for unresectable neuroendocrine metastases evidences feasibility and safety of this surgical approach in highly selected patients. Kyun Hong comment page 2717 .